The Main Molecular Mechanisms Underlying Methamphetamine- Induced Neurotoxicity and Implications for Pharmacological Treatment - Yang, Xue; Wang, Yong; Li, Qiyan; Zhong, Yaxian; Chen, Liangpei; Du, Yajun; He, Jing; Liao, Lvshuang; Xiong, Kun; Yi, Chun-xia; Yan, Jie (Frontiers in Molecular Neuroscience, 2018)
Methamphetamine (METH) is a popular new-type psychostimulant drug with complicated neurotoxicity. In spite of mounting evidence on METH-induced damage of neural cell, the accurate mechanism of toxic effect of the drug on central nervous system has not yet been completely deciphered. Besides, effective treatment strategies toward METH neurotoxicity remain scarce and more efficacious drugs are to be developed. In this review, we summarize cellular and molecular bases that might contribute to METH-elicited neurotoxicity, which mainly include oxidative stress, excitotoxicity and neuroinflammation. We also discuss some drugs that protect neural cells suffering from METH-induced neurotoxic consequences. We hope more in-depth investigations of exact details that how METH produces toxicity in central nervous system could be carried out in future and the development of new drugs as natural compounds and immunotherapies, including clinic trials, are expected.